China’s Policy towards Taliban-Ruled Afghanistan - Rashida Anis; Saira Aquil (ASIAN Journal of International Peace & Security (AJIPS), 2024)
Historically, China’s relations with Afghanistan encompasses more than seven decades of bilateral relations. From 2014 onwards, a significant shift was reflected in the diplomatic relations from a less-engaged diplomatic stance to a far active engagement. However, in the wake of US forces’ withdrawal and the Taliban recapturing of Kabul, China’s foreign policy conduct towards Afghanistan has become a strange puzzle, which needs to be deeply studied and explored. China’s tacit recognition and tactful dealings with the Taliban regime demand a thorough analysis. Therefore, the objective of the present research is to analyze China’s foreign policy behavior towards Afghanistan under Taliban regime. To get in-depth analysis, this study has applied descriptive and analytical research design and has used the qualitative data collection and data analysis tools and techniques. The major findings of the research show China’s visible but a slight tilt towards Taliban since the latter took control in Afghanistan in August 2021. The study concludes that the major characteristic of the current China’s policy towards Afghanistan is a “cautious yet engaged” policy posture, primarily due to the strong interplay of core security challenges and economic interests, respectively.